Simple extension of Lemaitre's elastoplastic damage model to account for hydrolytic degradation - Eduardo A. Fancello (Latin American Journal of Solids and Structures)
Being motivated by the technological applications of bioabsorbable polymeric materials in the fields of biomechanics and medicine, this paper presents a simple but efficient extension of Lemaitre's elastoplastic damage model by incorporating a chemical-based (hydrolysis) degradation term. The aim is to allow the simulation of devices subjected to both mechanical and chemical environments. The model applicability is tested by a set of numerical finite-element examples. The encouraging results show expected adequate coupling between the elastoplastic and chemical damages. Although the model is presently restricted to linear kinematics, the basic idea can be extended to finite strains.